Nitrate Removal Using Photocatalytic Reduction Process with Ag-TiO2 Catalyst - โรจน์วิรุฬห์ ธรรมศักดิ์ (Srinakharinwirot University Engineering Journal, 2019)
This research aims to study the efficiency of nitrate (NO3- -N) removal by photocatalytic reduction process using Ag doped TiO2 (Ag-TiO2) nanopowder catalyst. The Ag-TiO2 was prepared by composite colloid deposition under low temperature with acid condition. Ag was doped into TiO2 film by 3 different amounts, i.e. 0.1%, 0.5% and 1.0% weight to volume. The physical characteristics of the catalyst prepared were investigated by X-ray fluorescence spectrometer (XRF) and Brunauer, Emmett and Teller analyser (BET) that can identified elements and specific surface area of the catalyst prepared. The results showed that all of Ag-TiO2 nanopowder catalyst has the required components. The efficiency of photocatalytic reduction process of nitrate removal was evaluated from nitrate removal with initial nitrate concentration of 100 mg.L-1 as N under UVA light source of 1,000 mW.cm-2. The highest efficiency of photocatalytic reduction process for nitrate removal was 97.55% within 180 min and the highest reaction rate for NO3- 1.08 mg.L-1 as N. In addition, the selectivity (S) of nitrogen conversion in photocatalytic reduction process 90 min were 7.17%, 2.30% and 90.53%, for nitrite , ammonia and nitrogen respectively